Internal corrosion of carbon steel pipelines for dense-phase CO2 transport in carbon capture and storage (CCS) – a review. (2nd January 2017) - Barker, R.; Hua, Y.; Neville, A.
Abstract : Carbon Capture and Storage (CCS) has been highlighted as a potential method to enable the continued use of fossil-fuelled power stations through the abatement of carbon dioxide (CO2 ). A complete CCS cycle requires safe, reliable and cost effective solutions for the transmission of CO2 from the capturing facility to the location of permanent storage. This publication presents a detailed review of the integrity risks posed to dense-phase CO2 pipelines in the form of internal corrosion. To begin, the current worldwide experience in handling dense-phase CO2 and the anthropogenic stream compositions expected from the different combustion techniques currently available are discussed. The anticipated compositions are then related to a number of tentative CO2 stream compositions available in open literature proposed by research institutes and pipeline operators. In subsequent sections, early laboratory and field corrosion experience relating to natural dense-phase CO2 transport for the purposes of enhanced oil recovery (EOR) are summarised along with more recent research efforts which focus on identifying the role of anthropogenic impurities in the degradation processes. For each system impurity, the reaction rates, mechanisms and corrosion product composition/morphology expected at the steel surfaces are discussed, as well as each component's ability to influence the critical water content required to initiate corrosion. Potential bulk phase reactions between multiple impurities are also evaluated in an attempt to help understand how the impurity content may evolve along a long-distance pipeline. The likelihood of stress-corrosion cracking and hydrogen-induced cracking is discussed and the various corrosion mitigation techniques which exist to control degradation to acceptable levels are reviewed. Based on the current research performed in the context of impure dense-phase CO2 corrosion, issues associated with performing laboratory experiments to replicate field conditions and the challenges such limitations present in terms of defining the safe operating window for CO2 transport are considered.